Connecting open data to open access publishing: TU Delft library perspective - Belliard, Frederique; de Leeuwe, Just; Wang, Yan (Septentrio Conference Series, 2022)
Open data is becoming more and more a recognised research output in the research life cycle. Research validation and replication depend on open data which enriches the research output. Open data goes beyond the traditional article and book publishing format. As such open data reinforces Open Access (OA) publishing, and OA publishing reinforces open data. Open data and OA publishing stimulate collaboration and increase both the impact of research findings and the visibility of researchers and research groups. In the past years, funders and institutions developed independently policies that support open data and OA publishing. Researchers are increasingly required to publish OA and make their data open. The question is how we can evaluate the impact of Open data on OA publishing. Subsequently, to what extent does OA publishing influence open data? At the TU Delft, 82% of peer-reviewed articles and 71% of conference papers are published OA in 2021, but how many of those publications refer to open data? We have no records and no traceability processes in place to answer this question. As a consequence, few datastewards took on themselves to count manually the number of OA publications that include open data. It is nevertheless clear some changes need to occur to help open data and OA publishing joining forces. The current challenges and barriers faced could be reduced with an increase in OA research outputs (OA books or educational resources), a change in research culture and a change in reviewers’ practices. Recognising and rewarding data publishing; credit data review activities; developing a different workflow of the review process if including data review and requiring different expertise from the reviewers on the data review (data management and research insights) are realistic options. In parallel, new features of innovation for the publishing platform (open data review workflow, link to datasets for download) and for data repositories (quality badge on reviewed datasets, flexibility of incorporating review changes) are worth exploring. There are few possible solutions or workaround available that could help all. We can make it easy for the researchers by connecting different blocks of open science and optimising the benefits with the Data Access Statement (DAS) as a standard section of the article template and with publishers providing a DAS template with basic requirements. For institutions, having a dashboard connecting all research outputs with DOIs together will be very beneficial. Another option is giving authors control of their publications by publishing their findings in an open peer-reviewed community-driven journal. Our framework for connecting open data to OA publishing includes an OA publishing platform, data and publication repositories, a funding policy for OA publishing, expertise in Open Science and research lifecycle; and collaboration.